Pengaruh Akuntabilitas Kinerja Instansi Pemerintah Terhadap Tingkat Kepuasan Masyarakat Di Lingkungan Bebidas Kelurahan Pegesangan Barat, Kota Mataram, NTB - Silmi, Hayatus; Zitri, Ilham (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2023)
This research aims to determine the accountability and performance of government agencies in the Bebidas environment, Pegesangan Baraat subdistrict, Mataram City, as well as the influence of accountability in the performance of government agencies on community satisfaction in the performance of government agencies in the Bebidas environment, Pegesangan Barat subdistrict, Mataram city, both partially and simultaneously. The type of research used is quantitative research methods. The population in this study was 1,559. Hypothesis testing was tested using the t test and F test. Based on the research results, it shows that the accountability and performance of government agencies is good. The results of hypothesis testing show that the accountability of government agency performance influences community satisfaction both partially and simultaneously.